2016
DOI: 10.1155/2016/3763250
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Evaluation of Contrast-Induced Acute Kidney Injury Rodent Models

Abstract: Contrast-induced acute kidney injury (CI-AKI) can occur in 3–25% of patients receiving radiocontrast material (RCM) despite appropriate preventive measures. Often patients with an atherosclerotic vasculature have to receive large doses of RCM. Thus, animal studies to uncover the exact pathomechanism of CI-AKI are needed. Sensitive and specific histologic end-points are lacking; thus in the present review we summarize the histologic appearance of different rodent models of CI-AKI. Single injection of RCM causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 160 publications
3
45
0
Order By: Relevance
“…The histopathological evaluation of liver and kidney of the experimental mice in this study revealed that daily oral administration of CELE for 28 days at 1000 mg/kg dose resulted in various hepatic and renal lesions. The significant hepatic degeneration and necrosis observed histopathologically in the group of mice administered with daily oral doses of CELE at 1000 mg/kg for 28 days were suggestive of toxic or adverse effects [ 7 , 50 , 51 , 68 , 69 , 70 ] of the extract on the animals, as earlier observed in the results of plasma biochemical parameters for hepatic injury markers (ALT and AST). Similarly, the renal tubular degeneration and necrosis observed in this research further supported the results of plasma biochemical parameters, providing further indication that administration of the extract at 1000 mg/kg is not safe [ 50 , 51 ] for the female ICR mice.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The histopathological evaluation of liver and kidney of the experimental mice in this study revealed that daily oral administration of CELE for 28 days at 1000 mg/kg dose resulted in various hepatic and renal lesions. The significant hepatic degeneration and necrosis observed histopathologically in the group of mice administered with daily oral doses of CELE at 1000 mg/kg for 28 days were suggestive of toxic or adverse effects [ 7 , 50 , 51 , 68 , 69 , 70 ] of the extract on the animals, as earlier observed in the results of plasma biochemical parameters for hepatic injury markers (ALT and AST). Similarly, the renal tubular degeneration and necrosis observed in this research further supported the results of plasma biochemical parameters, providing further indication that administration of the extract at 1000 mg/kg is not safe [ 50 , 51 ] for the female ICR mice.…”
Section: Discussionsupporting
confidence: 67%
“…Correspondingly, histopathological evaluation of liver and kidneys suggested that the extract at this high dose of 2000 mg/kg might have induced mild histopathological lesions in the liver and kidneys of the treated mice. The histopathological lesions observed in this study, including cytoplasmic vacuolation and eosinophilic cytoplasm, although not significant, may suggest that the plant extract at 2000 mg/kg exhibited some degree of degenerative and necrotic effects [50,51] on the liver and kidney of the treated mice. The significant differences in the liver injury markers observed in this study contradicts the earlier reports by Khoo et al [12], where administration of 5000 mg/kg aqueous extract of C. nutans did not cause any significant changes in the levels of AST, ALT, ALP and total bilirubin between the treated and untreated groups of rats; this may perhaps be due to the differences in the extraction solvents, as water has less ability to extracts phytochemicals compared to ethanol [30,52,53].…”
Section: Discussionmentioning
confidence: 49%
“…Experimental details are provided in the Supplementary Appendix. 14,16,32,33 The study was approved by the Institutional Animal Care and Use Committee of Rush University in Chicago.…”
Section: Animal Model Of Acute Kidney Injurymentioning
confidence: 99%
“…In diagnosis of renal diseases, parameters such as volume and volume ratios, histomorphometric structure, and relative organ weight of kidneys are of great importance [4,19] . Changes in cortex and medulla of the kidney indicate pathological changes.…”
Section: Discussionmentioning
confidence: 99%